Comparative logarithmic studies on the relation between body weight and brain mass in birds (Gallus gallus) - Watanabe, I. (My University, 1975)
The author presents a systematic study on the body and brain growth in birds (Gallus gallus). He carried out logarithmic calculation of the absolute figures found, and comes to the conclusion that the increase of body weight and brain weight develop differently from each other.
Comparative logarithmic studies on the relation between body weight and brain mass in birds (Gallus gallus)